• 2√6-√20 / 2√5+√24 * (11+√30)

Ответы 1

  •  \frac{(2 \sqrt{6} - 2 \sqrt{5} )(2 \sqrt{5 }  -  2 \sqrt{6)}   }{(2 \sqrt{5} + 2 \sqrt{6})(2 \sqrt{5} - 2 \sqrt{6}  )  }  \times  \frac{ - (20 - 8 \sqrt{30}  + 24)}{24 - 20}  =  \frac{ - 4(11 -  \sqrt{30}) }{4}  = ( \sqrt{30}  - 11)(11 +  \sqrt{30} ) = 121 - 30 = 91
    • Автор:

      itsy
    • 5 лет назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years